EXPERIMENTAL STUDY ON THIN WALL CRACK ARREST BASED ON COATING TECHNOLOGY (MT) - JIANG JinDe; REN YunPeng; LU ChongShao; ZHU QingYu; ZHANG DongXu (Jixie qiangdu)
Due to long-term alternating load, engineering thin-walled structures will produce fatigue cracks, and most of them are penetrative cracks, which will lead to difficult repair and irreplaceable problems in engineering. Therefore, a coating technology is proposed to repair and crack arrest thin-walled structures. Thin plate test pieces related to practical engineering were made, and cracks were preset. The test piece was going to be subjected to the first-order bending resonance state and the excitation test with the foundation excitation of 10g on the vibration test bench until cracks appear. Two kinds of coatings, NiCrAl coating and NiCrAl transition layer + ZrO2 functional layer composite coating, were applied to the test piece by double-sided spraying method to repair the crack, and the excitation test was repeated. Comparing the crack propagation time and propagation rate of the test piece before and after coating, the influence of NiCrAl coating and ZrO2 coating on the crack propagation of the thin-walled plate test piece was analyzed. The crack arrest effect of the coating on the thin-walled plate is verified.